Escaping unsustainable digital interactions: Toward "more meaningful" and "moderate" online experiences. Issue 165 (September 2022) - Widdicks, Kelly; Remy, Christian; Bates, Oliver; Friday, Adrian; Hazas, Mike
Highlights: Moderate, meaningful digital designs could reduce some environmental and user harms. Participants share what digital technology use is, and is not, meaningful to them. Participants practically design for moderate and meaningful use of technology. Challenges exist beyond user experience that impact moderate and meaningful designs. Designs for moderate and meaningful use could include "internet speed bumps." Abstract: Growing and even excessive use of digital technology has unquestionably fuelled demand for digital devices and online services leading to a wide range of societal and environmental impacts. In sustainability terms, ICT as a whole is estimated to produce up to nearly 4% of global greenhouse gas emissions. As presumed responsible innovators, the HCI community should now consider design strategies that will reduce use and demand for digital technology for the good of both its users and the planet—strategies perhaps even seen as retrogressive in an era where digital technology is constantly implicated in innovation and economic growth. Prior work has noted the potential to design "more moderate" interactions for sustainability, simultaneously addressing negative societal impacts on users' wellbeing, relationships, productivity at work, and privacy. In this paper, we explore how we may design intentionally moderate digital interactions that retain our participants' "more meaningful" experiences. We report on the outcomes of two design workshops to uncover experiences of meaningful device and service use, to inform practical designs for 'moderate and meaningful' interaction. From this, we offer design recommendations that aim to address the multiple negative impacts that digital technology can create, and discuss the possible barriers to these designs.